Gaslighting, Misogyny, and Psychological Oppression. (9th March 2019) - Stark, Cynthia A
Abstract: This paper develops a notion of manipulative gaslighting, which is designed to capture something not captured by epistemic gaslighting, namely the intent to undermine women by denying their testimony about harms done to them by men. Manipulative gaslighting, I propose, consists in getting someone to doubt her testimony by challenging its credibility using two tactics: "sidestepping" (dodging evidence that supports her testimony) and "displacing" (attributing to her cognitive or characterological defects). I explain how manipulative gaslighting is distinct from (mere) reasonable disagreement, with which it is sometimes confused. I also argue for three further claims: that manipulative gaslighting is a method of enacting misogyny, that it is often a collective phenomenon, and, as collective, qualifies as a mode of psychological oppression.